Shrinkage, swelling and apparent specific gravity of red gum (Eucalyptus tereticornis Smith) (INNOTEC, 2013)
With the aim of contributing to the knowledge of the behavior of Eucalyptus tereticornis wood in Uruguay, a study of linear and volumetric shrinkage and swelling at different conditions of relative humidity at a temperature of 25 °C was made. From these data, a partial isotherm was built giving importance to the equilibrium moisture conditions in which it is possible to find products with this wood, e.g. floors and decks. Five trees from a 50 years old shelter belt located in Durazno were randomly selected. Discs were collected at two heights in each tree from which specimens were prepared for shrinkage and swelling test. It was found that the basic apparent specific gravity was 0,630, 0,859 at 12% and 0,872 at 15% of moisture content. The radial, tangential and volumetric shrinkage was 7,04%,14,7% and 20,64%, respectively, and the radial, tangential and volumetric swelling was 7,61%, 17,61% and 26,62%. It was observed an expected difference between the curve of sorption and desorption in the studied range of relative humidity from 53%to 84%.
Keywords: Hysteresis; equilibrium moisture; isotherm; density